MORPHOLOGICAL VARIATION OF GLYPTOTHORAX PLATYPOGON VALENCIENNES, 1840 IN SERAYU RIVER BANJARNEGARA AND RINGIN RIVER SEMARANG CENTRAL JAVA - Maizul, Riza; Wahyudewantoro, Gema; Setyawati, Siti Mukhlishoh; Hidayat, Saifullah (BRIN Publishing (Penerbit BRIN), 2023)
Glyptothorax platypogon is freshwater fish, it’s potential to be an ornamental fish. Its need to be protected from extinction because population in other areas is till abundance. G. platypogon has reported that it's in Serayu River and based on pre-research observations found in Ringin River, Semarang, Central Java. The differences in the geographic location of the two rivers have the potential for the emergence of morphological variations of G. platypogon. Research on the morphology study of the G. platypogon from the Serayu River in Banjarnegara and the Ringin River has been conducted. This study describe morphological variations and provide information about the phenetic relationship between them. Sampling was carried out at Serayu River and Ringin River by direct observation and collection methods in the Field then continued at the Structure Laboratory of Biology Department State Islamic University Walisongo for observed morphometric and meristic,including 43 characters. Data was analyzed with the Kruskall Wallis test, Mann Whitney U test, PCA (Principal Component Analysis) and UPGMA (Unweighted Pair Group Arithmetic Average Method). The result showed that there were high morphological variations in the Allopatric population in Serayu River and Ringin River and there were low morphological variations in the Sympatric population in Serayu river. There were two clad taxa branching groups from Serayu and Ringin population which show morphological variation. UPGMA analysis and Euclidean distance show the population of Serayu River and Ringin River have a close phenetic relationship.